Packing the donor heart: Is SherpaPak cold preservation technique safer compared to ice cold storage. Issue 8 (20th May 2022) - Bitargil, Macit; Haddad, Osama; Pham, Si M.; Garg, Neha; Jacob, Samuel; El‐Sayed Ahmed, Magdy M.; Landolfo, Kevin; Patel, Parag C.; Goswami, Rohan M.; Leoni Moreno, Juan Carlos; Yip, Daniel S.; Sareyyupoglu, Basar
Abstract: Introduction: The present study aimed to compare the clinical outcomes of heart transplant patients whose donor hearts were preserved with the SherpaPak controlled cold organ system versus the conventional ice storage technique. Methods: All patients undergoing heart transplantation at our center between January 2019 and April 2021 were divided into two groups according to the technique used during donor heart preservation and transport. The first group consisted of 34 SherpaPak controlled temperature preservation patients, and the second group consisted of 47 patients where the conventional three bags and ice technique was utilized during organ transportation. The two groups were compared based on demographics, operative details, and postoperative outcomes. Results: There were no significant differences between the groups regarding Vasoactive Inotropic Score (VIS), Primary Graft Dysfunction (PGD), and the need for a transient pacer. However, the VIS, PGD, and pacing trends were lower in the SherpaPak patients even though the total ischemic and cardiopulmonary bypass times were significantly longer. Furthermore, SherpaPak patients exhibited a shorter stay in the ICU with no severe PGD and mortality. Conclusion: The SherpaPak donor heart preservation provides safe outcomes in heart transplant patients. Further research is needed to utilize this method for longer durations of ischemic time and expand travel distances for organ transportation.